2021
DOI: 10.1002/pc.26332
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, thermal, and mechanical properties of cellulose nanocrystal reinforced poly(lactic acid) and poly(butylene adipate‐co‐terephthalate): A comparative study on common and novel solvent casting methods

Abstract: The mechanical and thermal properties of semicrystalline (sc) and amorphous (a) poly(lactic acid), PLA, and poly(butylene adipate-co-terephthalate), PBAT, and their nanocomposites containing 1 and 3 wt% CNCs, prepared through solvent casting methods using one (N,N-dimethylformamide [DMF]) or two (dimethyl sulfoxide (DMSO), and tetrahydrofuran (THF)) solvents were analyzed. Differential scanning calorimetry (DSC) showed that the total amount of crystals of the scPLA/CNC nanocomposites increased, whereas it decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 64 publications
(155 reference statements)
0
2
0
Order By: Relevance
“…The enhancements observed in the storage modulus were ascribed to the reinforcing impact of CNW‐g‐PBA and the ameliorated stress transfer at the interface. Multiple studies have reported a comparable rise in the storage modulus of polymer composites upon the incorporation of micro and nano‐sized fillers into the polymer matrix 23,33 . The E ′ value of PLA/C‐g‐P‐7 was observed to be lower than that of PLA/C‐g‐P‐5.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The enhancements observed in the storage modulus were ascribed to the reinforcing impact of CNW‐g‐PBA and the ameliorated stress transfer at the interface. Multiple studies have reported a comparable rise in the storage modulus of polymer composites upon the incorporation of micro and nano‐sized fillers into the polymer matrix 23,33 . The E ′ value of PLA/C‐g‐P‐7 was observed to be lower than that of PLA/C‐g‐P‐5.…”
Section: Resultsmentioning
confidence: 95%
“…Multiple studies have reported a comparable rise in the storage modulus of polymer composites upon the incorporation of micro and nano-sized fillers into the polymer matrix. 23,33 The E 0 value of PLA/C-g-P-7 was observed to be lower than that of PLA/C-g-P-5. This can be attributed to the agglomeration of nanocellulose.…”
Section: Samplesmentioning
confidence: 91%